2005
DOI: 10.2139/ssrn.3183564
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for the Low Rate of Conviction in the Vaw Cases and Inconsistencies in the Legislative Framework

Abstract: The work publishes the research findings following Quantitative and Qualitative research methodologies. The conclusion drawn by the authors on the basis of the collected data and comparisons among different legislative provisions does not constitute any former legal or other professional advice. BRAC University shall not assume any liability for action taken on the basis of information, findings or opinions in this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Although the prevalence of IPV against women is extremely high in rural Bangladesh, a study revealed that only 1.2% of the survivors used to seek legal remedies (Arefin & Karim, 2021). Both arrest and conviction rates related to different IPV-related offenses are also low in the country (Naznin & Sharmin, 2018). As reported by the Women and Children Repression Prevention Tribunal of Bangladesh, less than 3% of the cases of violence against women in 2019 had resulted in a conviction (as cited from Amin, 2019).…”
Section: Laws On Ipv In Bangladeshmentioning
confidence: 99%
“…Although the prevalence of IPV against women is extremely high in rural Bangladesh, a study revealed that only 1.2% of the survivors used to seek legal remedies (Arefin & Karim, 2021). Both arrest and conviction rates related to different IPV-related offenses are also low in the country (Naznin & Sharmin, 2018). As reported by the Women and Children Repression Prevention Tribunal of Bangladesh, less than 3% of the cases of violence against women in 2019 had resulted in a conviction (as cited from Amin, 2019).…”
Section: Laws On Ipv In Bangladeshmentioning
confidence: 99%